Uncovering Hidden Histories: Evaluating Preservice Teachers' (PST) Understanding of Local Indigenous Perspectives in History Via Digital Storytelling at Australia's Sovereign Hill. Issue 3 (3rd July 2019) - Weuffen, Sara; Cahir, Fred; Barnes, Alice; Powell, Bryon
ABSTRACT: Non-Indigenous-led organizations and education programs have long been criticized for sanitized teachings of Aboriginal perspectives in history, while scholarship touts the transformative benefits offered up via decolonial and immersive pedagogical approaches. In this case study, we explore the impact of a cross-cultural venture, titled Hidden Histories: The Wadawurrung People, between a living history museum, the local Aboriginal community, and a regional university on teacher preparedness to incorporate Aboriginal perspectives in history curricula. Through a cultural interface lens, we examine the ontological and epistemological developments of 112 preservice teachers postinteraction with an intercultural digital-kinaesthetic education tool. Our findings suggest that PSTs enjoy engaging with the tool, yet while on site, they prefer to immerse themselves in the museum environment. Our findings indicate also, however, that the tool is an accessible cross-cultural predatory tool that encourages a lifelong commitment to integrating Aboriginal perspectives in history curricula.